Natural Resources Law in Australia: Principles and Practices - Danial Kelly (Jambe Law Journal, 2018)
What is the jurisprudential approach taken to Natural Resources Law in Australia? The ultimate source of law in Australia is Commonwealth of Australia Constitution Act however the Constitution does not specifically include an environment or natural resources power and the Commonwealth government can only make laws under the heads of power provided by the Constitution. This paper considers how natural resources law has developed as environmental protection law, especially the Environment Protection and Biodiversity Conservation Act. Also discussed is the approach taken by the Northern Territory of Australia in relation to natural resources law. The discussion unearths the developing jurisprudence in Australian natural resources law that seems to increasingly favour environmental protection over human development.